The Influence of Flood Education on Student Awareness at State Junior High School 34 Medan - Meutia Nanda; Annisa Ananda; Laila Silvia Br Sitepu; Putri Anggi Marsanda Hrp; Alda Khairani; Chairunnisa Anggina; Khairani Putri (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
loods are the most frequent hydrometeorological disasters in Indonesia and have a wide impact on health, environment, and educational activities. This study aims to determine the influence of flood education in the school environment on the awareness of SMPN 34 Medan students. The research method uses a quantitative approach with a one group pre-test post-test design. The research subjects were 31 students in grade IX. Data collection was carried out using knowledge questionnaires before and after the provision of flood education. The results of the study showed that there was an increase in students' knowledge after being given flood education, including understanding of the causes of flooding increased from 77.4% to 96.8%, understanding of the role of waste in drainage blockages increased from 71.0% to 93.5%, and understanding of preparedness measures before and during floods increased from 74.2% to 90.3%. In addition, students' understanding of the impact of floods on health has also increased from 67.7% to 87.1%. Based on the results of the statistical test using a paired t-test, a p-value of < 0.05 was obtained, which shows that there is a significant influence on increasing students' knowledge and awareness in flood disaster mitigation efforts. This counseling has proven to be effective in improving students' disaster literacy. Therefore, it is recommended that flood education activities be carried out in a sustainable and integrated manner in school activities to maintain and increase student preparedness for flood disaster risks.